Moulding training for communities around Politeknik Negeri Samarinda - Anun Sudibyo; Bernardo Sandrini Salasa (Universitas Muhammadiyah Magelang, 2021)
The abundance of wood supplies as the main raw material in the manufacture of furniture should encourage people in Samarinda City to look at this business as a promising business. But in reality, the development of the furniture business in Samarinda City is still far behind when compared to other cities. One of the factors causing the underdevelopment of this industry is the low capacity of human resources. Realizing the problems, the community service team in collaboration with partners (Meubel Berkah Ghegan) aimed to provide molding training to the community around the Politeknik Negeri Samarinda. The training is carried out in seven work steps, socialization, determination of furniture types, design / design, material checking, wood cleaning and drying, material processing, and finishing. This service activity improves the skills of participants in designing and producing furniture, increases knowledge about furniture making techniques with modern tools, and provides insight related to furniture business opportunities in Samarinda City.